Liquid Metal Embrittlement (LME) Akibat Kontaminasi Tembaga Pada Pipa Baja Api 5L x70 Dengan Pengelasan Busur Rendam[Liquid Metal Embrittlement (LME) Caused By Copper Contamination On Api 5l X 70 Steel Processed By Submerged Arc Welding (SAW)] - Priyono, Budi (Jurnal Metalurgi, 2015)
In this study, we conducted a study of failures in the form of copper metal penetration into the metal welds low-alloy carbon steel (C-Mn-Mo) which caused cracking in the process of making pipe with submerged arc welding or SAW (submerged arc welding). Such failures are known as liquid metal embrittlement (LME). In this study, the failure is caused by the quality LME copper layer, where LME characterized by red spot on the surface of the weld metal. LME failure mechanisms that have been studied in this research is a copper layer on the electrode is oxidized to form CuO compounds, brought into the molten metal, and surface weld metal. CuO compounds are then reduced again by the slag to metallic Cu in a liquid state. In this condition will occur metallic copper penetration into the weld metal through the grain boundaries which are known as liquid metal embrittlement (LME). LME failure in this study was due to the strong effect of the welding electrodes coating, the copper layer should be separated or broken before entering into an arc welds and trapped in the molten slag as an impurity.